Specific Selection of FFT Amplitudes from Audio Sports and News Broadcasting for Classification Purposes - Poulos, Marios; Bokos, George; Kanellopoulos, Nikolaos; Papavlasopoulos, Sozon; Avlonitis, Markos (Journal of Graph Algorithms and Applications, 2007)
In this paper we investigate the problem of classification between sports and news broadcasting. We detect and classify files that consist of speech and music or background noise (news broadcasting), and speech and a noisy background (sports broadcasting). More specifically, this study investigates feature extraction and training and classification procedures. We compare the Average Magnitude Difference Function (AMDF) method, which we consider more robust to background noise, with a novel proposed method. This method uses several spectral audio features which may be considered as specific semantic information. We base the extraction of these features on the theory of computational geometry using an Onion Algorithm (OA). We tested the classification procedure as well as the learning ability of the two methods using a Learning Vector Quantizer One (LVQ1) neural network. The results of the experiment showed that the OA method has a faster learning procedure, which we characterise as an accurate feature extraction method for several audio cases. <!—->